BRAIN DAMAGE AND LANGUAGE PRODUCTION: A STUDY ON THE NEUROLOGICAL ASPECT OF LANGUAGE - Ignas Loy Semana (Jurnal Pendidikan dan Kebudayaan Missio, 2018)
Language is closely related to human being. All human being normally speak at least one language. It is hard to imagine much significant social, intellectual, or artistic activity taking place in the absence of language. The possession of language distinguishes humans from other animals. Even to understand our humanity we must understand the language that makes us human. Language is also connected to brain. It is believed that language is a distinctive piece of biological make up of our brains. In the contrary, if humans have disaster in their brain then automatically that disaster will bring certain negative effects in comprehending and producing language (speech production). This study discusses the relation between brain (biological aspect of language) and language production (linguistic aspect) that is so-called neurolinguistics. The aim of the study is to show the negative effect of damaged brain in comprehending and producing language